Prinsip dasar kebijakan pembangunan berkelanjutan berwawasan lingkungan - Sugandhy, Aca.; Hakim, Rustam (Jakarta : Bumi Aksara, 2007)
On environmental aspects and policy of sustainable development in Indonesia.
Includes bibliographical references (p. 143-146)
Keywords: Environmental policy -- Indonesia; Sustainable development -- Indonesia